Mapeamento e análise do cenário editorial e literário da Serra Gaúcha (2000-2016) - Cecchin, Aline Brustulin (My University, 2018)
This thesis focuses on the investigation of the editorial scenario of the Serra Gaúcha/RS/Brazil. Understanding literature as a system that is formed from a wide and complex network of relations, the objective is to map and analyze the literary mechanisms of production and publication in the region, from the perspective of its writers and editors. Initially, it is based on an extensive research on writers and works that compose the literary scenery from 2000 to 2016, with the purpose of structuring the panorama of publications and fiction producers in the region. Then personal interviews with 25 writers and 4 editors are carried out, in order to verify how they perceive their work in the literary system under discussion. Finally, the interviews are tabulated and analyzed according to the sociology of literature. Particular social, historical and cultural factors of the region, as well as the conditions of production, diffusion, reading and literary public, compose the investigative elements of this research and collaborate to understand the literary life in Serra Gaúcha, at the present time.
O foco desta tese centra-se na investigação do cenário editorial da Serra Gaúcha/RS/Brasil. Ao compreender a literatura como um sistema que se forma a partir de uma ampla e complexa rede de relações, tem-se como objetivo mapear e analisar os mecanismos de produção, publicação e circulação literária na região, sob o ponto de vista de seus escritores e editores. Inicialmente, parte-se de uma ampla pesquisa sobre escritores e obras que compõem a paisagem literária serrana do ano 2000 até 2016, com o propósito de estruturar o panorama de publicações e de produtores de ficção na região. Em seguida, realizam-se entrevistas pessoais com 25 escritores e 4 editores, com o intuito de verificar como eles percebem sua atuação no sistema literário em questão. Finalmente, as entrevistas são tabuladas e analisadas à luz da sociologia da literatura. Fatores sociais, históricos e culturais específicos da região, assim como as condições de produção, difusão, leitura e público literário, compõem os elementos investigativos desta pesquisa e colaboram para que se compreenda a vida literária na Serra Gaúcha, na atualidade.
Keywords: Editores e edição - Serra, Região (RS); Escritores e editores; Sociologia da literatura; Publishers and publishing - Serra, Região (RS) - Brazil; Author and publisher; Sociology in literature